Adolescents Are Less Physically Active Than Adults After Anterior Cruciate Ligament Reconstruction. Issue 2 (21st February 2022) - Kuenze, Christopher; Collins, Katherine; Triplett, Ashley; Bell, David; Norte, Grant; Baez, Shelby; Harkey, Matthew; Wilcox, Luke; Lisee, Caroline
Background: Sources of physical activity (PA) and motivation for return to sport after anterior cruciate ligament reconstruction (ACLR) differ between adolescents and adults. It is unclear whether these differences influence participation in PA during the first year after ACLR when individuals are transitioning from rehabilitative care to unrestricted activity. Purpose: To compare device-assessed measures of PA between adolescents and adults at 6 to 12 months after ACLR. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Included were 22 adolescents (age, 15.9 ± 1.2 years; time since surgery = 8.0 ± 2.1 months) and 23 adults (age, 22.5 ± 5.0 years; time since surgery = 8.2 ± 2.1 months) who were cleared for unrestricted PA after primary unilateral ACLR. Participants were considered physically active if they met their age-specific United States Department of Health and Human Services PA guidelines. Participants wore an accelerometer-based PA monitor for at least 7 days. Daily minutes of moderate to vigorous–PA (MVPA) and daily step counts were reported and compared between age groups using analysis of covariance, with monitor wear time and sex included as covariates. The association between age group and meeting age-specific PA guidelines was assessed using binary logistic regression and reported as an odds ratio. Results: Adults with ACLR participated in 16 minutes more MVPA per day (49 ± 22 vs 33 ± 16 minutes per day; P < .001) and took 2212 more steps per day (8365 ± 2294 vs 6153 ± 1765 steps per day; P < .001) when compared with adolescent participants. In addition, 83% of adults were physically active, compared with 9% of adolescents (odds ratio = 60.2; 95% CI, 7.6-493.4). Conclusion: Adolescents with ACLR were less physically active than adults with ACLR, and only 9% of adolescents met aerobic PA guidelines. This is concerning because PA patterns adopted early in life are predictive of PA patterns in adulthood. Our findings indicate a need to better understand underlying causes of reduced PA among adolescents with ACLR and to develop intervention strategies that promote engagement in adequate PA after rehabilitation.